Integrated nutrient management in broccoli (Brassica oleracea var. italica) - SINGH, D P; RAJIV, RAJIV; TOMAR, SAURABH; KUMARI, MEENAKSHI (The Indian Journal of Agricultural Sciences, 2021)
Field experiment was conducted during rabi 2016-17 to 2018-19 to determine the effect of INM on of yield and economic attributes of broccoli at Vegetable Farm, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur. Nine different treatment combinations, viz. full recommended dose of NPK through chemical fertilizer, FYM@ 20 tonnes /ha, FYM @ 10 tonnes/ha+ half NPK through chemical fertilizer, neem cake @ 5 q/ha, neem cake @ 2.5q/ha + half NPK through chemical fertilizer, vermicompost @ 5 t/ha, vermicompost @ 2.5 t/ha + half NPK through chemical fertilizer, poultry manure @ 5 t/ha and poultry manure @ 2.5 t/ha + half NPK through chemical fertilizer were tested in randomized block design with four replications under AICRP on Vegetable Crops. Aishwarya varietyof broccoli was transplanted at a spacing of 45 cm Ã— 45 cm. Results of the experiment revealed that the application ofvermicompost @ 2.5 t/ha + half NPK through chemical fertilizer recorded significantly highest head weight (386.80g), total yield (204.76 q/ha), net income (` 108832/ha) and B:C ratio (3.15). Therefore, the practice of vermicompost integration with half dose of chemical fertilizers may be recommended to exploit the better eco-friendly economic yield of broccoli.